Effects of USP25 knockout on the gut microbial diversity and composition in mice - Jinqiu Li; Zhonghui Chen; Xingchen Yan; Qizhou Chen; Cirong Chen; Huan Liu; Jianlin Shen (BMC Microbiology)
Abstract Background The gut microbiota plays a crucial role in host health. Recent study revealed that ubiquitin-specific protease 25 (USP25) deficiency affected colonic immune responses and resistance to certain bacterial infection. This study aimed to investigate the impact of USP25 gene deletion on the gut microbiota of mice, utilizing 16 S rRNA amplicon sequencing and metagenomic sequencing to provide a comprehensive analysis of microbial diversity, composition and functional characteristics. Methods We collected fecal samples from 10 wild type (WT) C57BL/6J mice and 10 USP25−/− mice (C57BL/6J-Usp25em1cyagen) for 16 S rRNA amplicon sequencing. Subsequently, the 6 of the 20 samples underwent further analysis using metagenomic sequencing. Results Our results revealed significant differences in the gut microbiota between USP25 knockout (KO) mice and wild-type (WT) controls, with KO mice exhibiting 1,858 unique amplicon sequence variants (ASVs) compared to 1,723 in WT mice. Notably, the KO group displayed a higher tendency for biofilm formation and a greater proportion of gram-negative bacteria, while the WT group demonstrated enhanced stress tolerance and a higher presence of gram-positive bacteria. Functional prediction analyses indicated an increase in antibiotic resistance genes in the KO mice, particularly for tetracycline, cephalosporin, and sulfonamides, suggesting a potential risk for clinical antibiotic treatment efficacy. Moreover, KEGG pathway enrichment analysis revealed significant enrichment for fructose and mannose metabolism, streptomycin biosynthesis in the KO group. Furthermore, an increase in protective microbes alongside a decrease in potential pathogens in the KO microbiota hinted at altered immune responses due to USP25 deletion. Conclusion Our findings elucidate the essential role of USP25 in modulating gut microbiota composition and function, providing insights for future therapeutic strategies targeting gut microbiota in disease contexts. Clinical trail number Not applicable.